A Diptera Cecidomyiidae, Dasineura gleditchiae (O sten Sacken), new for Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
The Diptera Cecidomyiidae Dasineura gleditchiae (Osten Sacken) has been found on Gleditschia triacanthos in northern Italy and information is given on its biology and the damage it can cause.This northern American species was found in gardens and nurseries, where trees of Gleditschia have been imported from Belgium and Holland, which are probably the insect's first stop in Europe from its region of origin.